Study of copper thick film metallization on aluminum nitride. (February 2020) - Hlina, Jiri; Reboun, Jan; Hamacek, Ales
Abstract: This paper is focused on the study of copper thick film metallization on AlN. The copper metallization was realized by Thick Printed Copper (TPC) technology. The copper films were printed with a new adhesion copper paste designed for both AlN and Al2 O3 substrates. Scanning electron microscopy (SEM) and energy-dispersive X-ray spectroscopy (EDS) analyses on cross-sections have shown that the paste adhesion to AlN and Al2 O3 is provided by different bonding mechanisms. The influence of different adhesion mechanisms on electrical and mechanical properties as well as the morphology of copper films on AlN and Al2 O3 substrates are described in this paper. Graphical abstract: Image, graphical abstract